Allergies/asthma and root resorption: a systematic review - Cibelle Cristina Oliveira dos Santos; Silvio Augusto Bellini-Pereira; Melany Clarissa Gamez Medina; David Normando (SpringerOpen, 2021)
Abstract Background This review synthesizes the available evidence about the predisposition of individuals with asthma or allergies to orthodontically induced inflammatory root resorption (OIIRR) and possible factors related to root resorption that were investigated in the included studies, such as the type of malocclusion, duration of orthodontic treatment, and tooth units. Material and methods Six electronic databases and partial gray literature were searched without date or language restrictions until September 2020. Prospective and retrospective observational cohort and case-control studies were included. The risk of bias (RoB) was assessed using the checklists from the Joanna Briggs Institute and the certainty of the evidence using the GRADE tool. To complement the case-control studies, the odds ratio (OR) of the individuals with allergies/asthma to develop root resorption was calculated. Results Six studies were included. One study with low RoB, one with moderate, and one with high RoB stated that allergic patients did not report a greater chance of developing OIIRR (OR = 1.17 to 2.10, p = 0.1 to 1), while only one study with low RoB reported that individuals with allergies tend to develop root resorption (OR = 2.4, 95% CI = 1.08-5.37). Three studies with low RoB and one with moderate showed no significant association between asthma and OIIRR (OR = 1.05 to 3.42, p = 0.12 to 0.94). No association was identified between the type of malocclusion and the degree of OIIRR. Uniradicular dental units and a prolonged treatment time seem to be associated with an increased risk of resorption. The certainty of the evidence was considered low for both exposure factors. Conclusion Evidence with a low level of certainty indicates that individuals with allergies or asthma are not more predisposed to OIIRR. Uniradicular teeth and long-term orthodontic treatments are associated with a higher risk of OIIRR. Systematic review registration PROSPERO CRD42020188463